2020
DOI: 10.1101/2020.05.26.20104497
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge and attitude towards COVID-19 in Bangladesh: Population-level estimation and a comparison of data obtained by phone and online survey methods

Abstract: Adherence of people to the guidelines and measures suggested in fighting the ongoing COVID-19 pandemic is partly determined by the Knowledge, Attitude, and Practices (KAP) of the population. In this cross-sectional study, we primarily addressed two key issues. First, we tried to determine whether there is a significant difference in the estimated COVID-19 knowledge level from the online and phone survey methods. Second, we tried to quantify the knowledge and attitude of COVID-19 in Bangladeshi adult population… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
33
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 20 publications
9
33
2
Order By: Relevance
“…Subjects with "good knowledge" or "high scores for fear" were more likely to believe that COVID-19 can be controlled and that a collective effort can contain the spread of the disease. Similar studies in Bangladesh, India, and China all found similar results regarding the relationship between knowledge and fear of COVID-19 regarding "practices", [16,25,30], and our study reported similarities to previous studies across the world [23,24]. Our study found that 37.5% of women reported "staying home", and 36.8% reported wearing masks in public places.…”
Section: Discussionsupporting
confidence: 88%
“…Subjects with "good knowledge" or "high scores for fear" were more likely to believe that COVID-19 can be controlled and that a collective effort can contain the spread of the disease. Similar studies in Bangladesh, India, and China all found similar results regarding the relationship between knowledge and fear of COVID-19 regarding "practices", [16,25,30], and our study reported similarities to previous studies across the world [23,24]. Our study found that 37.5% of women reported "staying home", and 36.8% reported wearing masks in public places.…”
Section: Discussionsupporting
confidence: 88%
“…Despite the reason that more than 3/4 th (82.2%) of the total participants have completed primary school or above and it has been more than half a year since the declaration of the pandemic, only 142 [(42.9%) range 0-13 and mean 8.73±2.64] of the participants had an acceptable level of knowledge score regarding COVID-19. This finding is much lower than other studies [26][27][28][32][33][34][36][37][38][39][40][41] in different parts of the world. The reason might be due to inadequate access to information.…”
contrasting
confidence: 71%
“…The discrepancy might be due to differences in cut-values used to categorize the knowledge levels, sample size, and sociocultural various between study settings. However, this result is higher than a study conducted in Syrian residents (60%) [39], USA (58%) [40], Bangladesh (48.3%) (57.6%) (10%) [24,41,42], three Middle Eastern countries (66.1%) [43], Makerere University Teaching Hospitals (66%) [25], Pakistan (51.8%) [44]. The differences in level of knowledge have been subjected to variation in the cut-values (i.e.…”
Section: Discussionmentioning
confidence: 81%